Comparison of Low-Molecular-Weight Heparins Prepared From Ovine Heparins With Enoxaparin. (12th April 2019) - Chen, Jianle; Yu, Yanlei; Fareed, Jawed; Hoppensteadt, Debra; Jeske, Walter; Kouta, Ahmed; Jin, Caijuan; Jin, Yongsheng; Yao, Yiming; Xia, Ke; Zhang, Fuming; Chen, Shiguo; et al.
Heparin and its low-molecular-weight heparin derivatives are widely used clinical anticoagulants. These drugs are critical for the practice of medicine in applications, including kidney dialysis, cardiopulmonary bypass, and in the management of venous thromboembolism. Currently, these drugs are derived from livestock, primarily porcine intestine and less frequently bovine intestine and bovine lung. The worldwide dependence on the pig as a single dominant animal species has made the supply chain for this critical drug quite fragile, leading to the search for other sources of these drugs, including the expanded use of bovine tissues. A number of laboratories are now also examining the similarities between heparin and low-molecular-weight heparins prepared from porcine and ovine tissues. This study was designed to compare low-molecular-weight heparin prepared from ovine heparin through chemical β-elimination, a process currently used to prepare the low-molecular-weight heparin, enoxaparin. Using top-down, bottom-up, and compositional analyses as well as bioassays, low-molecular-weight heparin derived from ovine intestine was shown to closely resemble enoxaparin. Moreover, the compositions of daughter low-molecular-weight heparins prepared from three unfractionated ovine parent heparins were compared. Ovine enoxaparins had similar molecular weight and in vitro anticoagulant activities as Lovenox. Some disaccharide compositional, oligosaccharide composition at the reducing and nonreducing ends and intact chain compositional differences could be observed between porcine enoxaparin and ovine low-molecular-weight heparin. The similarity of these ovine and porcine heparin products suggests that their preclinical evaluation and ultimately clinical assessment is warranted.